A DvT-based clinical assessment of toxic stress in young children. Issue 2 (1st October 2021) - Johnson, David Read; Pitre, Renée; Davis, Catherine
A clinical assessment procedure is described for identifying possible sources of toxic stress among young children (ages 3‐10), using a semi-structured modification of Developmental Transformations. This modification consists of improvisational play combined with a pre-determined sequence of roles symbolic of common adverse childhood experiences of neglect or emotional or physical threat. While conducting this procedure, the therapist carefully observes the client's responses within the play to note the presence of play disruptions (e.g. hesitation, shift of scene and/or emotional arousal). These shifts may arise from prior experiences that remain distressing to the client and might merit further exploration. A review of the literature concerning toxic stress and assessments of children (particularly those that are play-based), along with an illustration of the clinical assessment, are presented. Strategies for follow-up and early intervention possibilities are highlighted. Key ethical considerations of this procedure are also discussed.